Energy-aware retransmission scheme for multimedia delivery over wireless networks - Abdallah, Deema (2011)
Traditional error recovery schemes such as automatic repeat request (ARQ) and incremental redundancy rely on immediate retransmissions to deal with bit errors or packet losses. This immediate retransmission approach leads to increased energy consumption and performance degradation for multimedia communications over wireless networks especially when the probability of data error is high. Moreover, retransmissions negatively impact the performance of other mobile nodes due to the nature of resource sharing in wireless networks. In this work, an energy-aware retransmission scheme is designed, implemented, and evaluated. The proposed scheme adapts packet retransmissions based on both the received signal level at the mobile nodes and the data reception success rate. Performance results using ns-2 simulations demonstrate notable reduction in energy consumption. Results also show that the proposed scheme outperforms the default 802.11b medium access control (MAC) protocol in terms of packet delay which is an important metric for multimedia applications.